LITERASI DIGITAL PESANTREN: PERUBAHAN DAN KONTESTASI - Ali Ja’far (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2019)
This article explains about digital literacy in Pesantren as part of modernization, and also describes about the academic changes and the digital contestation as well as its impact to Pesantren’s tradition. The writer takes an example in Pesantren Al-Anwar 3, Sarang-Rembang that have been experiencing academic transformation and being different from the previous institution and the writer finds some points. First , modernization and digital literacy bring about diversification of knowledge where the santri (pesantren students) could freely access the information through online. Secondly, digital literacy in pesantren has much to do with the prominent figure and implemented as a wise way to control and consume the information. Thirdly digital literacy is a good chance to spread the narration of tolerance Islam, inclusivism, the idea about nationality, however this need a serious attention an guidance such the process of reading , filtering and re-checking. Through participatory observation and in depth interview, the writer would give the depiction about digital literacy in Pesantren Al-Anwar 3, the curriculum, experience of changing, digital contestation also explaining how the santri and pesantren utilize and develop the digital literacy.